METHODOLOGICAL PROBLEMS OF STATISTICAL ASSESSMENT OF THE SOCIO-ECONOMIC DEVELOPMENT OF REGIONS - Elena N. Volkova (Статистика и экономика)
In recent years, increased attention is paidto the various aspects of applied analysisof individual subjects of our country. In thiscontext, the great scientiﬁc and practicalinterest is the systematization of problemsgeneralizing the statistical characteristicsof the socio-economic development at theregional level.